2008
DOI: 10.1504/ijfsnph.2008.023011
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid fibrils: potential food safety implications

Abstract: Abstract:The demonstration of oral Amyloid-A (AA) fibril transmissibility has raised food safety questions about the consumption of amyloidotic viscera. In a presumed prion-like mechanism, amyloid fibrils have been shown to trigger and accelerate the development of AA amyloidosis in rodent models. The finding of amyloid fibrils in edible avian and mammalian food animal tissues, combined with the inability of cooking temperatures to eliminate their amyloidogenic potential, has led to concerns that products such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…(2007) have provided experimental evidence which reveals that an amyloid-containing food (Foie gras) product can substantially hasten the development of protein amyloidosis in a susceptible mouse population . Further, research reports have also indicated that amyloid deposits present in cattle can also cause amyloidosis in a mouse model. , Considering the results reported by these studies, aspartame consumption seems to be capable of predisposing serious consequences both directly and indirectly. Direct defects can arise from the formation of cytotoxic aspartame fibrils and toxic amyloids of other essential proteins and peptides due to aspartame-driven amyloid cross-seeding.…”
Section: Discussionmentioning
confidence: 99%
“…(2007) have provided experimental evidence which reveals that an amyloid-containing food (Foie gras) product can substantially hasten the development of protein amyloidosis in a susceptible mouse population . Further, research reports have also indicated that amyloid deposits present in cattle can also cause amyloidosis in a mouse model. , Considering the results reported by these studies, aspartame consumption seems to be capable of predisposing serious consequences both directly and indirectly. Direct defects can arise from the formation of cytotoxic aspartame fibrils and toxic amyloids of other essential proteins and peptides due to aspartame-driven amyloid cross-seeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence of amyloid fibrils in milk, we have speculated that fibrils may form in certain dairy products. If tested and proved correct, then further research to minimize the fibril content of dairy products may be advisable (Greger, 2008 …”
Section: Discussionmentioning
confidence: 99%
“…Healthy mice exposed orally to AA fibrils did not develop amyloidosis, whereas those additionally receiving a concurrent inflammatory stimulus developed a pronounced disease within days ( 83 ). Conditions associated with elevated SAA levels may include chronic infections, as well as non-infectious chronic inflammatory diseases, and certain tumors ( 84 ). The concentration of SAA can drastically increase at an acute inflammation as a response to cytokines, especially IL-1, IL-6, and TNF-α ( 85 ).…”
Section: Four Good Reasons Why the Commercialization Of Milk From Cow...mentioning
confidence: 99%